Responses to training in cross-country skiers - Gaskill, S. E.; Serfass, R. C.; Bacharach, D. W.; Kelly, J. M. (Medicine & Science in Sports & Exercise, 1999)
PURPOSE: This study evaluated whether cross-country skiers who did not respond positively to a training program consisting of high volume and low intensity would improve if high-intensity training volume was doubled during a subsequent training year. METHODS: During the first year of the study, cross-country skiers (N = 14) were evaluated for VO2max, VO2threshold, lactate response, max arm power, and competitive results after a standard training program. During the second year, the athletes were divided into a control group (athletes who had responded well to the training) and a treatment group (athletes who had responded poorly to the training). The control group (N = 7) repeated the previous year's training program. The treatment group (N = 7) was given a modified training program which increased high-intensity training time as a percentage of total training from < 17% to > 35% and decreased low-intensity training volume 22%. RESULTS: The treatment group, using the high-intensity training program, demonstrated significantly improved VO2max, VO2threshold, max arm power, and competitive results (P < 0.05). CONCLUSIONS: Increased volume of high-intensity training may improve competitive results in cross-country skiers who fail to respond to increased volume of low-intensity training.